Thermal and crystalographic studies of mixture La2O3-SrO prepared via reaction in the solid state - Marques, Rodrigo Fernando Costa [UNESP]; Zorel, H. E. [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Jafelicci, M. [UNESP]; Paiva-Santos, C. O. [UNESP]; Varanda, L. C. [UNESP]; Godoi, R. H M [UNESP] (Kluwer Academic Publ, 1999)
The compound obtained via state solid reaction of the La2O3 and SrO oxides and expose the room atmosphere shows the crystallographic data of the compound reported as La2SrOx. However, thermogravimetric, differential thermal analysis and XRD with controlled temperature indicated that the stoichiometry of the compound is 2La(OH)(3)-SrCO3, which structural parameters were determined by using the Rietveld method. It was verified that when the compound exposed at room atmosphere, the mixture oxide absorbs H2O and CO2 producing hydroxide and carbonate of lanthanum and strontium, respectively, which thermal decomposition occurs by the same steps, producing the La2O3-SrO.
Keywords: Carbon dioxide; Crystallography; Differential thermal analysis; Gas absorption; Lanthanum compounds; Pyrolysis; Stoichiometry; Strontium compounds; Thermogravimetric analysis; Water absorption; X ray diffraction analysis; Reversible thermal decomposition; Mixtures